Change in the status of internally displaced Bosniaks of the Srebrenica municipality in the Tuzla canton during the period 2005-2015 - Suljić, Alija; Kadušić, Alma; Mešanović, Dževad; Smajić, Sabahudin (Journal for Geography, 2016)
The war during the period 1992-1995 has caused massive forced migrations of the population in Bosnia and Herzegovina and in this period about 1.2 million people fled beyond the borders of Bosnia and Herzegovina while about 1 million were displaced inside the country. After the Dayton Peace Agreement, there started the process of return of refugees and displaced persons in Bosnia and Herzegovina. However, even after more than 20 years since the signing of the Agreement a significant number of refugees and displaced persons has not returned to their pre-war places of residence. This paper explores the number and the change in the status of the internally displaced Bosniaks of Srebrenica Municipality in the period 2005-2015, those who were residing in Tuzla Canton of the Federation of Bosnia and Herzegovina. According to the Federal Ministry of Refugees and Displaced Persons in Tuzla Canton, in 2005, the status of internally displaced persons had 2016 households with a total of 5549 members, and by 2015 this status has kept 1099 households with a total of 2867 members. The aim of this paper is to point out to some more significant factors that led to a reduction in the number of Bosniaks from the area of Srebrenica municipality who had the status of internally displaced persons in Tuzla Canton.
Keywords: Bosniaks; people of Srebrenica; internally displaced persons; status; Tuzla Canton; Srebrenica municipality; municipalities of the Tuzla Canton